Using optical coherence tomography to rapidly phenotype and quantify congenital heart defects associated with prenatal alcohol exposure. Issue 4 (13th March 2015) - Karunamuni, Ganga; Gu, Shi; Doughman, Yong Qiu; Noonan, Amanda I.; Rollins, Andrew M.; Jenkins, Michael W.; Watanabe, Michiko
Abstract : Background: The most commonly used method to analyze congenital heart defects involves serial sectioning and histology. However, this is often a time‐consuming process where the quantification of cardiac defects can be difficult due to problems with accurate section registration. Here we demonstrate the advantages of using optical coherence tomography, a comparatively new and rising technology, to phenotype avian embryo hearts in a model of fetal alcohol syndrome where a binge‐like quantity of alcohol/ethanol was introduced at gastrulation.Results: The rapid, consistent imaging protocols allowed for the immediate identification of cardiac anomalies, including ventricular septal defects and misaligned/missing vessels. Interventricular septum thicknesses and vessel diameters for three of the five outflow arteries were also significantly reduced. Outflow and atrioventricular valves were segmented using image processing software and had significantly reduced volumes compared to controls. This is the first study to our knowledge that has 3D reconstructed the late‐stage cardiac valves in precise detail to examine their morphology and dimensions.Conclusions: We believe, therefore, that optical coherence tomography, with its ability to rapidly image and quantify tiny embryonic structures in high resolution, will serve as an excellent and cost‐effective preliminary screening tool for developmental biologists working with a variety of experimental/disease models. Developmental Dynamics 244:607–618, 2015 . © 2014 Wiley Periodicals, Inc. Key Findings: We used optical coherence tomography (OCT), a novel biophotonic tool, to analyze congenital heart defects (CHDs) in an embryonic disease model. Avian embryos developed CHDs associated with Fetal Alcohol Syndrome after being exposed to binge volumes of ethanol at gastrulation. OCT allowed for the rapid, consistent identification of CHDs such as ventricular septal defects and outflow defects. Using OCT images, we measured valve volume, interventricular septum thickness and vessel diameters which were significantly reduced after ethanol exposure. This user‐friendly, cost‐effective technique will be invaluable to developmental biologists seeking to streamline the analysis of embryonic models with the added benefit of precise, reliable quantification.